Identification of Fungus Issue in the Government’s Purpose-Built Office (GPBO) - A Case Study of Suruhanjaya Pilihan Raya (SPR) Malaysia Tower - ZAINUDDIN, IRSYAD; MOHD AMIN, MUHAMMAD ALIF; NIK LI, NIK ADAM; MOHAMMAD, HAIRUDDIN (Multidisciplinary Applied Research and Innovation, 2025)
Fungal issue in GPBO may affected health and also the integrity of the building. Therefore, the research investigates the issue through 3 main objective; 1) To identify the generic type of fungus and the factors contributing to fungus issue in building.   2)  To populate fungus-related cases in Suruhanjaya Pilihan Raya (SPR) Malaysia Tower.  3) To suggest proper rectification based on the populated data from Suruhanjaya Pilihan Raya (SPR) Malaysia Tower.  Inline, to achieve the stated objective, a series of methodologies were undertaken, namely; document analysis, document analysis (past research), document analysis (suggest rectification), which are conducted accordingly. The results shows that, there were certain type of fungus that growth in Suruhanjaya Pilihan Raya (SPR), these fungus also growth extremely in many levels in that buiding, proper moisture control and ventilation in the SPR Building Tower are needed as a rectification. In conclusion, this research provides insights enabling homeowners and construction professionals to conduct proactive periodic maintenance, thereby enhancing home quality and safety.